2011
DOI: 10.1142/s0219477511000570
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography (Emg) Signal Classification Based on Detrended Fluctuation Analysis

Abstract: Electromyography (EMG) signal is a useful signal in various medical and engineering applications. To extract the useful information in the EMG signal, feature extraction method should be performed. The extracted features of the EMG signal are usually calculated based on linear or statistical methods, but the EMG signal exhibits the nonlinear and more complex in the properties. With recent advances in nonlinear analysis we are proposing the study of the EMG signals from upper-limb movements using Detrended Fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Although many advanced time-scale and non-linear algorithms have been developed in the past decade to analyze and identify surface electromyography (EMG) signal [1,2], features based on the amplitude of surface EMG signals have been still widely used as a control input in muscle-computer interfaces (MCIs) [3][4][5][6][7]. One of the major advantage reasons is about the lower complexity and computational cost of the EMG amplitude estimators compared to the advanced time-scale and non-linear algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Although many advanced time-scale and non-linear algorithms have been developed in the past decade to analyze and identify surface electromyography (EMG) signal [1,2], features based on the amplitude of surface EMG signals have been still widely used as a control input in muscle-computer interfaces (MCIs) [3][4][5][6][7]. One of the major advantage reasons is about the lower complexity and computational cost of the EMG amplitude estimators compared to the advanced time-scale and non-linear algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Phinyiomark uses DFA in several works to classify low level sEMG signals [35] [48] [49] [50]. In [35] 8 gestures were classified with the wrist, hand and forearm using weak upper-limb sEMG signals for five channels, for 20 healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that, DFA has better cluster separability than HG (Phinyomark et al, 2011d), as well as classification performance (Phinyomark et al, 2012d). On the other hand, features based on a magnitude detector provide better performance in the classification of high-level EMG signal patterns than fractal features.…”
Section: Feature Set 2: Low-level and High-level Surface Emg Signalsmentioning
confidence: 98%
“…Based on our previous work (Phinyomark, Phukpattaranont, Limsakul, & Phothisonothai, 2011d), the minimum box size n min is set at four, the maximum box size n max is set at one-tenth of the signal length, and the box size increment is based on a power of two. A least-square fit, which is applied to the profiles y k , is the quadratic polynomial fit.…”
Section: Computation Of Emg Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation